(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In this study outcome from morphological and biochemical tests (such as those for shape,arrangement, colonies, temperature, growth, form, margin, elevation, indole production, methyl red,Voges-Proskauer, citrate utilisation, starch hydrolysis, urease production, hydrogen sulphide production,catalase activity, lactose, glucose, and sucrose fermentation) were used to identify and characterise purebacterial isolates chosen for this study.